2022
DOI: 10.1002/smll.202202253
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembled Artificial DNA Nanocompartments and Their Bioapplications

Abstract: was previously inseparably fused with all the rest of the world, set itself apart from the environment surrounding it." In this way, initial forms of self-organized systems may have acquired the capability to distinguish the in from the out, and later, the self from the nonself, traveling the path that eventually led to the smallest structural and functional unit of all living beings, the cell. [3] At a smaller scale, various cellular compartments and transmembrane cavities evolved to ensure the correct funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 252 publications
0
15
0
Order By: Relevance
“…In addition to τR, the folding of the i-motif can contribute to reduced water activity due to an ordered layer of water on the surface caused by nanoconfinement conditions. The restricted space makes the water molecules more ordered than the bulk solution affecting τM and thus affecting relaxivity 36 . Water molecules in enclosed environments have a considerably different diffusion than in bulk, which leads to increased relaxivities 37 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition to τR, the folding of the i-motif can contribute to reduced water activity due to an ordered layer of water on the surface caused by nanoconfinement conditions. The restricted space makes the water molecules more ordered than the bulk solution affecting τM and thus affecting relaxivity 36 . Water molecules in enclosed environments have a considerably different diffusion than in bulk, which leads to increased relaxivities 37 .…”
Section: Resultsmentioning
confidence: 99%
“…Their structure can keep the enzyme functioning properly while enabling the communication between internal and external substances allowing continuous reactions . At present, the main approaches to assembling functional enzymes in ASCs are encapsulation and piggyback. , Considering that ASCs need to be heterologously expressed, regulated, and assembled into intracellular compartments, most researchers choose proteins or polymers as carriers for construction . This section introduces the major ASCs that have been or potentially will be artificially introduced into MCFs to promote product synthesis (Figure ).…”
Section: Designing Artificial Subcellular Compartments To Enhance The...mentioning
confidence: 99%
“…This provides a highly predictable intermolecular interaction and makes DNA strands natural building blocks for on-demand assembly. 15,16 Seeman et al demonstrated in the early 1980s that by breaking the sequence symmetry of Holliday junctions, one could lock the mobile junction to obtain an immobile structure. 17,18 The immobile Holliday junctions could be considered as a crossover between two DNA duplexes, while stronger junctions such as double crossover, 19 triple crossover, 20 and six-helix bundles 21 have been subsequently constructed by connecting multiple duplexes.…”
Section: Origin and Basic Principlesmentioning
confidence: 99%